The Effect of Dexmedetomidine as a Sedative Agent for Mechanically Ventilated Patients With Sepsis: A Systematic Review and Meta-Analysis - Wang, Caimu; Chen, Qijiang; Wang, Ping; Jin, Weisheng; Zhong, Chao; Ge, Zisheng; Xu, Kangmin (Frontiers in Medicine, 2021)
.Abstracts Purpose: Dexmedetomidine has been shown to improve clinical outcomes in critically ill patients. However, its effect on the septic patients remains controversial. Therefore, the purpose of this meta-analysis was to assess the effect of dexmedetomidine as a sedative agent for mechanically ventilated patients with sepsis. Methods: We searched PubMed, Embase, Scopus, and Cochrane Library from inception through May 2021 for randomized controlled trials enrolled mechanically ventilated, adult septic patients comparing dexmedetomidine with other sedative or placebo. Results: A total of nine studies involving 1134 patients were included in our meta-analysis. The overall mortality (RR 0.97, 95%CI 0.82 to 1.13, P=0.67, I2=25%), length of intensive care unit stay (MD -1.12, 95%CI -2.89 to 0.64, P=0.21, I2=71%), incidence of delirium (RR 0.95, 95%CI 0.72 to 1.25, P=0.70, I2=0%) and delirium free days (MD 1.76, 95%CI -0.94 to 4.47, P=0.20, I2=80%) were not significantly different between dexmedetomidine and other sedative agents. Alternatively, the use of dexmedetomidine was associated with a significant reduction in the duration of mechanical ventilation (MD -0.53, 95%CI -0.85 to -0.21, P=0.001, I2=0%) and inflammatory response (TNF-α: MD -5.27, 95%CI -7.99 to -2.54, P<0.001, I2=0%; IL-1β: MD -1.25, 95%CI -1.91 to -0.59, P<0.001, I2=0%). Conclusions: For septic patients, the use of dexmedetomidine as compared to other sedative agent has no effect on all-cause mortality, length of intensive care unit stay, incidence of delirium and delirium free days. But the dexmedetomidine was associated with reduced duration of mechanical ventilation and inflammatory response.